(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A non-banking financial organization called Cebuana Lhuillier provides services like e-loading, pawnbroking, insurance, money remittance, and bill payment. Cebuana Lhuillier has successfully positioned itself as the Philippines’ top one-stop financial shop, driven by its mission to give more Filipinos access to financial solutions and its vision to become the best and most preferred micro-financial and business-to-business. Cebuana Lhuillier, the largest microfinance institution in the Philippines, has significantly encouraged innovation and entrepreneurship among its staff members by utilizing digital technologies. The evaluation of the promotional activity was "often" in terms of personal selling, advertising, Sales Promotion, public relations, and direct marketing. The biggest challenge encountered by the consumer is the slowness of the process when there are a lot of people in Cebuana Lhuillier. Cebuana Lhuillier needs to enhance the promotions that it offers to its customers. The recommendation that the researcher will make in Cebuana Lhuillier Ph1 is first to increase the space of Cebuana Ph1 so that there are more customers who can transact and not crowd inside. Second, increase the number of employees within a Cebuana branch to speed up every transaction; and last, have good communication or relationship with a customer so that there is no misunderstanding between the customer and the employee.